Peningkatan Motivasi Belajar IPA Melalui Model Pembelajaran Project Based Learning pada Masa Pandemi Covid-19 bagi Siswa SMP Negeri 4 Gunungsari - Lilik Handayani (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to increase the motivation to study science through the learning model of project based learning on plant propagation material by artificial vegetative means in the Covid-19 pandemic conditions. This research method uses descriptive methods. The subjects in this study were 41 students of SMPN 4 Gunungsari, with a total of 41 people. The instruments of this study used a questionnaire and the data analysis technique used descriptive analysis. The results of this study indicate that students are motivated to carry out project work carried out, carried out without any burden and produce maximum results, as well as being an assessment of science practice exams at the end of learning at school.